The false justification test - Cruz Del Carpio, Ian (2023)
The main characteristic of unlawful acts is that the perpetrator seeks their secrecy; in this sense, it is important to obtain few means of evidence to reveal the act directly. In this context, circumstantial evidence is a key element in uncovering the illegal act and its perpetrator. Within the framework of inductive reasoning, several indicia have been formulated, one of which stands out because it allegedly undermines the right of defence of the accused. We refer to the indicia of false justification, which is established when the defendant’s alibi is shown to be false and this aspect is used against the defendant.